Las inversiones a plazo fijo y su relación con la gestión financiera de la COAC Minga Ltda., durante el periodo 2020-2022 - Guaman Duche, Jaime Rolando (2024)
ABSTRACT: The objective of this research work is to evaluate fixed-term investments and their relationship with the financial management of the "Cooperativa de Ahorro y Crédito Minga Ltda." during the period 2020 - 2022, which is why it was carried out based on the deductive method with a mixed approach of non-experimental design, based on field and documentary research, where financial statements are the primary source of information and through a documentary review the data analysis technique was applied. Furthermore, the interview was conducted to obtain relevant information on financial management from the financial manager responsible for managing the institution's economic information. Based on the application of horizontal analysis, the trend and growth of fixed-term deposits could be determined, with results that indicate that during the periods 2020 and 2021, the growth of these deposits was USD 2,190,072.20, while for the period 2021 and 2022, increased to USD 4,689,943.85, indicating significant growth in the last period which contributes positively to the institution. Regarding applying the liquidity ratio, it can be determined that the cooperative can cover short-term debts without compromising liquidity since its current ratio is greater than 1. In contrast, applying the profitability ratio determined that the cooperative's costs are managed effectively. In addition, the operating margin is positive due to the increase in its income; however, through the application of the ROE, it was determined in the last period that the entity is unprofitable due to inadequate management of expenses; this provides valuable information to issue criteria regarding the financial management of the cooperative.